Social anxiety disorder: prevalence and dominant factor among adolescents in urban and rural school - Priasmoro, Dian Pitaloka; Kusuma, Ikhwan Yuda; Asri, Yuni (Intelektual Pustaka Media Utama, 2024)
In the age range of 16-18 years, commonly known as adolescence, individuals undergo a period of self-discovery in their socio-emotional development. Failures during this process can lead to individuals experiencing anxiety in social interactions, which can have a negative impact on their mental health. The Indonesia National Adolescent Mental Health Survey (I-NAMHS), findings also indicate that the most prevalent mental disorder among adolescents is anxiety disorder (a combination of social phobia and generalized anxiety disorder), is equivalent to 15.5 million. The widespread use of the internet and social media, on one hand, has led to a high dependency on smartphones among teenagers, causing them to spend more time interacting in the virtual world. Over an extended period, this condition can lead to social anxiety due to the fear of failure and lack of success. The objective of this research is to explore whether there is a difference in social anxiety among teenagers living in rural or urban areas, related to factors such as the duration of smartphone usage, school activities, and so on. The results of this research are crucial for providing feedback to high schools, especially for early detection of potential anxiety symptoms from the beginning, in order to prevent and provide appropriate treatment for social anxiety, thus not affecting students' academic achievements. It is recommended that schools conduct early detection measures.